2019
DOI: 10.1144/jgs2019-021
|View full text |Cite
|
Sign up to set email alerts
|

Continental rifting at magmatic centres: structural implications from the Late Quaternary Menengai Caldera, central Kenya Rift

Abstract: The structural evolution of calderas in rifts helps to characterize the spatiotemporal relationships between magmatism, long wavelength crustal deformation and the formation of tectonic deformation zones along the rift axis. We document the structural characteristics of the c. 36 ka old Menengai Caldera located within a young zone of extension in the central Kenya Rift. Field mapping and high-resolution digital surface models show that NNE-striking Holocene normal faults perpendicular t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 122 publications
0
11
0
Order By: Relevance
“…It has, however, been suggested that due to the alternating layers of volcanics and sedimentary strata of the intrarift units of the NKR, such steep dip estimates from purely volcanic settings cannot be transferred to the NKR (Le Gall et al., 2000). At the surface, extensional fractures are suggested to partly accommodate the near‐surface extension at subvertical fault scarps (e.g., Acocella et al., 2003; Corti, 2009), and such extensional fractures are very common in the Kenya Rift (e.g., Atmaoui & Hollnack, 2003; Muirhead et al., 2016; Riedl et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It has, however, been suggested that due to the alternating layers of volcanics and sedimentary strata of the intrarift units of the NKR, such steep dip estimates from purely volcanic settings cannot be transferred to the NKR (Le Gall et al., 2000). At the surface, extensional fractures are suggested to partly accommodate the near‐surface extension at subvertical fault scarps (e.g., Acocella et al., 2003; Corti, 2009), and such extensional fractures are very common in the Kenya Rift (e.g., Atmaoui & Hollnack, 2003; Muirhead et al., 2016; Riedl et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…We applied classical techniques in tectonic geomorphology summarized in seminal textbooks [45][46][47] for mapping newly-identified faults and remapping structures from previous studies at a uniform 1:25,000 scale. We rely on our past experience in mapping active faults in different tectonic environments using field observations and remote sensing data 16,[48][49][50][51][52][53][54][55][56] , in addition to the criteria used in previous active fault databases [57][58][59][60][61] . We paid special attention to interpreting fault trace continuity using a uniform mapping scale based on the surface expression of faults, not the inferred seismogenic expression at depth.…”
Section: Methodsmentioning
confidence: 99%
“…Further applications have been, for example, assessing anthropogenic factors in triggered and induced seismicity 12 such as stress changes to the crust caused by hydroelectric reservoirs, underground gas storage, groundwater pumping, or fracking 13 , 14 . Many geothermal fields occur in tectonically-active regions and maps of active faults have been used both for exploration and selection of drilling sites 15 , 16 as well as for reservoir modelling during exploitation 17 , 18 . Active fault databases have been also used in studies of volcanotectonic interactions and structural control on volcanism in rifts 19 and arcs 20 , in the interpretation of present-day stress indicators 21 , 22 as well as to infer sources of pre-instrumental earthquakes 23 and the response of groundwater to near and farfield earthquakes 24 .…”
Section: Background and Summarymentioning
confidence: 99%
“…As such, Quaternary volcano‐sedimentary units are areally restricted to the inner graben, which has been the focus of densely spaced normal faulting that has resulted in a horst‐and‐graben landscape (Hackman, 1988; McCall, 1967; Thompson & Dodson, 1963). Furthermore, the inner graben has been characterized by volcanic, seismic, and hydrothermal activity during the last 2 Ma (Clarke et al., 1990; Riedl et al., 2020; Tongue et al., 1992).…”
Section: Geological Backgroundmentioning
confidence: 99%